Health Inequalities in British Nurses using Census derived databases linked to an adjusted UK Index of Multiple Deprivation - Ball, Will; Kyle, Richard; Atherton, Iain; Dougall, Nadine (International Journal of Population Data Science, 2018)
Introduction Scottish health outcomes are worse than in England and Wales. This variation remains after controlling for deprivation, which explains less excess mortality now than previously. Alternative cross-national deprivation measures have limitations which may explain some of this trend. Recent policy interventions to reduce inequalities have not been effective. Objectives and Approach This study aims to test a recently developed measure of area deprivation, the UK adjusted Index of Multiple Deprivation which has been linked to National Census derived Longitudinal Studies in England, Wales and Scotland. This adjusted measure is consistent across UK countries and addresses some limitations of previously utilised area measures of deprivation. This study also aims to test whether characteristics of Nurses are protective against inequalities in health. This study will test whether Nurses are more socio-economically homogenous and whether higher health literacy is protective against the social gradient in health outcomes. Results (1) Comparing Nurses to Non-Nurses in Scotland we found that they have systematically different demographic characteristics. Nurses are; older on average, more likely to be female, more likely to own their home, more likely to live in less deprived areas and they report better self-rated health. (1a) Correlation tests will examine the strength of relationship between health and Deprivation quintile for these groups. (2) Comparing Self-Rated Health of Scottish Nurses with English and Welsh Nurses will determine whether any ‘excess’ in worse health outcomes exists and (2a) if an excess does exist, whether the UK consistent deprivation measure can account for this. Analysis is currently ongoing and will be completed, with full results cleared for dissemination through disclosure control, prior to conference. Conclusion/Implications This study implements methods which provide a basis for cross-national comparison of inequalities using individual-level data and a consistent measure of area deprivation. Results from this study may also permit recommendations to improve the effectiveness of policy aimed at improving population health and reducing socio-economic inequalities in health.